2020
DOI: 10.1016/j.isprsjprs.2020.10.007
|View full text |Cite
|
Sign up to set email alerts
|

SAR analysis of wetland ecosystems: Effects of band frequency, polarization mode and acquisition dates

Abstract: The availability of high spatial resolution synthetic aperture radar (SAR) sensors with a wide range of acquisition modes has increased greatly over the past decade and contributed significantly to the study of wetland ecosystems. However, the relative influence of acquisition configurations (i.e. band frequency, polarization mode, number of acquisition dates) in wetland analysis remains poorly explored. This article investigated the relative influence of X-/C-band frequency, dual-/quad-polarization and single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…The NL-SAR, which gave the best results in the segmentation of watercourses images located in marshes [20], also in our study provided high classification accuracy. The most often used filter in wetlands classification is the refined Lee filter [4], [15] with a 5×5 window [2] or a 7×7 window [5]. Several studies applied the boxcar filter with a 5×5 [7], [16], [17] window size, or the improved Lee sigma filter with a 3×3 [3] or 5×5 [1] window.…”
Section: A Effect Of Speckle Filtering and Filter Window Size On Clas...mentioning
confidence: 99%
See 3 more Smart Citations
“…The NL-SAR, which gave the best results in the segmentation of watercourses images located in marshes [20], also in our study provided high classification accuracy. The most often used filter in wetlands classification is the refined Lee filter [4], [15] with a 5×5 window [2] or a 7×7 window [5]. Several studies applied the boxcar filter with a 5×5 [7], [16], [17] window size, or the improved Lee sigma filter with a 3×3 [3] or 5×5 [1] window.…”
Section: A Effect Of Speckle Filtering and Filter Window Size On Clas...mentioning
confidence: 99%
“…I N RECENT years, many studies focused on the application of different synthetic aperture radar (SAR) data in wetlands mapping using various acquisition setups. The studies showed an impact on the classification accuracy of the SAR band, polarization mode, multiple acquisition dates [1]- [5], and incidence angles of the beam [6], [7]. At the same time, the selection of the polarimetric processing parameters of the SAR images was rarely justified, while only several studies demonstrated that these parameters influence the workflow.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies that used fully polarimetric SAR imagery have noted the influence of different polarimetric scattering features on wetland classification results [ 26 , 27 ]. For example, Millard et al combined SAR and Lidar data to achieve higher accuracy [ 28 ].…”
Section: Introductionmentioning
confidence: 99%